Dynamics of Dry-Down in Seed, Head and Stalk from Sunflower Genotypes Sprayed with Chemical Desiccants After Physiological Maturity - Cyntia Lorena Szemruch; Federico García; Sebastian Zuil; Christian Teysseire; Juan P Renzi; Miguel A Cantamutto; Santiago Renteria; Deborah P Rondanini (Turkish Journal of Agriculture: Food Science and Technology)
Chemical desiccation can advance the sunflower harvest time. Paraquat has been extensively used, but other less risky chemicals, as Carfentrazone and Saflufenacil, can rise as an alternative. Moisture levels of seed, head and the upper portion of stalk are all relevant for mechanical harvesting, but dry-down dynamics of each tissue is unknown. The aim was to study the dry-down dynamics of seed, head and stalk in sunflower genotypes sprayed with Paraquat, Carfentrazone and Saflufenacil after physiological maturity. Seven experiments were carried out in the field in Argentina (from 29 to 39º S) during 2014/2015 and 2015/2016. The genotypes used included hybrids and female inbred lines of both oil and confectionery types. The dry-down of sunflower plant was accelerated by desiccants with Paraquat, reducing seed and stalk moisture to a greater extent. The head moisture remained very high (>80 and 70%) during several days after application, without differences among desiccants and control. Dynamics of seed, head, and stalk moisture was not associated to vapor pressure deficit or meteorological conditions after chemical application. Loss of green color of leaves was not a reliable indicator of seed dry-down dynamics. Seed germination was not affected by chemical desiccation on either oil-type or confectionery female plants. Under broad conditions of these experiments, the Paraquat was effective for seeds/grains and stalks drying in both sunflowers hybrids and inbred lines. The slowly drying of heads makes it necessary to continue investigating with new doses and combinations of desiccants to ensure an optimal harvest. Desiccants were safe for seed germination, which benefits their usefulness in the seed industry.